Tuberculin PPD Potency Assays in Naturally Infected Tuberculous Cattle as a Quality Control Measure in the Irish Bovine Tuberculosis Eradication Programme - Duignan, Anthony; Kenny, Kevin; Bakker, Douwe; Good, Margaret (Frontiers in Veterinary Science, 2019)
The Irish Bovine Tuberculosis (bTB) eradication programme operates under national legislation and fulfills OIE and EU trade requirements. Tuberculin purified protein derivative (PPD), a preparation obtained from the heat-treated products of growth and lysis of Mycobacterium bovis or Mycobacterium avium (as appropriate), is critical to the diagnosis of tuberculosis (TB). Standardization of Tuberculin PPD potency, the relative activity in sensitized animals compared to a reference standard, is essential to underpin the reliability of certification for international trade and to ensure that disease eradication programmes are effective and efficient. A Bovine International Standard Tuberculin PPD (BIS) was established by the WHO in 1986 and is used to determine comparative potencies of Tuberculin PPDs. Ideally, Tuberculin PPD potency should be evaluated in the species in which the tuberculin will be used but due to practical difficulties in performing potency assays in cattle, for routine PPD production, they are usually assayed in guinea pigs. Low potency tuberculin PPD is less efficient and thus inferior for bTB diagnosis. Difficulties experienced in the Irish bTB eradication programme have included the supply of sub-standard potency, and thus inferior, bovine (M. bovis) Tuberculin PPD in the late 1970s. The purpose of this paper is to outline the critical role of Tuberculin PPD assays carried out on naturally infected tuberculous cattle, as required by the OIE and under EU legislation in the quality control for the Irish Bovine Eradication Programme. Such assays ensure that the Tuberculin PPD used meets the diagnostic sensitivity and specificity requirements to underpin a successful national eradication programme.